Landscape context and microenvironment influences on liana communities within treefall gaps - Malizia, Agustina (2008)
How do gap aspect, openness, age and gap density in the surroundings affect diversity and composition of lianas within treefall gaps? Are the variation patterns in liana communities within treefall gaps associated with their climbing mechanisms?